A tale of absent flowers and naked seeds - Jutta, Mariam; Habau, Mohd Hazwan (University Putra Malaysia, 2012)
Empeng, a popular fried snack with a distinctive bitter taste, is made from the rolled, flattened nuts of the belinjau or melinjau tree (Gnetum gnemon.). These plants look just like other trees, with woody trunks, and branches and twigs bearing green leaves. But this is where the similarities cease - belinjau trees do not have flowers and thus do not form their fruits from flowers. What then, if not a flower, comes before the fruit? Instead of flowers they produce male and female reproductive structures in strobili or cones, a feature they share with conifers, cycads, gingkos and the curious Welwitschia.